Facile Synthesis, Characterization and Visible-Light Photocatalytic Performance of Ag3PO4 - Lin1, Li; Huang1, Manhong; Long2, Liping; Sun1, Zhe; Chen1, Donghui (Asian Journal of Chemistry, 2014)
Silver(I) phosphate (Ag3PO4) photocatalysts were synthesized via a facile solid phase ion-exchange method, X-ray diffraction, scanning electron microscopy and UV-visible diffuse reflectance spectroscopy (DRS) were used to characterize the as-prepared samples. The photocatalytic performance and mechanism of as-prepared samples were investigated by the degradation of tetracyclines in aqueous solution under visible light irradiation (l > 420 nm). The results indicated that the as-prepared samples were irregular spherical morphology with paticle size of 0.5-1.5 μm and exibited strong light absorbance in the visible light region. The superior photocatalytic activity and removal efficiency of total organic carbon (TOC) were also observed. The mechanism expriment results demonstrated that the O2•−, •OH and hole were all reactive oxygen species and the possible photocatalytic mechanism was proposed.